Genomic Characterization of the Taylorella Genus - Hébert, Laurent; Moumen, Bouziane; Pons, Nicolas; Duquesne, Fabien; Breuil, Marie-France; Goux, Didier; Batto, Jean-Michel; Laugier, Claire; Renault, Pierre; Petry, Sandrine (PLOS ONE, 2012)
The Taylorella genus comprises two species: Taylorella equigenitalis, which causes contagious equine metritis, and Taylorella asinigenitalis, a closely-related species mainly found in donkeys. We herein report on the first genome sequence of T. asinigenitalis, analyzing and comparing it with the recently-sequenced T. equigenitalis genome. The T. asinigenitalis genome contains a single circular chromosome of 1,638,559 bp with a 38.3% GC content and 1,534 coding sequences (CDS). While 212 CDSs were T. asinigenitalis-specific, 1,322 had orthologs in T. equigenitalis. Two hundred and thirty-four T. equigenitalis CDSs had no orthologs in T. asinigenitalis. Analysis of the basic nutrition metabolism of both Taylorella species showed that malate, glutamate and alpha-ketoglutarate may be their main carbon and energy sources. For both species, we identified four different secretion systems and several proteins potentially involved in binding and colonization of host cells, suggesting a strong potential for interaction with their host. T. equigenitalis seems better-equipped than T. asinigenitalis in terms of virulence since we identified numerous proteins potentially involved in pathogenicity, including hemagluttinin-related proteins, a type IV secretion system, TonB-dependent lactoferrin and transferrin receptors, and YadA and Hep_Hag domains containing proteins. This is the first molecular characterization of Taylorella genus members, and the first molecular identification of factors potentially involved in T. asinigenitalis and T. equigenitalis pathogenicity and host colonization. This study facilitates a genetic understanding of growth phenotypes, animal host preference and pathogenic capacity, paving the way for future functional investigations into this largely unknown genus.